Risky Play as an Educational Tool to Enhance Safety Awareness in Early Childhood - Sakinah Siregar (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Play is a highly important activity for children's growth and development, contributing to nearly every aspect of development physical-motor, language, cognitive, socio-emotional, and religious values. This study explores the benefits of risky play in safety knowledge education for early childhood, drawing on Piaget's cognitive development theory, Vygotsky's zone of proximal development, and Bandura's social learning theory. Using a qualitative case study approach, the findings show that risky play such as climbing, jumping from heights, and playing in open areas with minimal supervision enhances children's understanding of their own capability limits and potential hazards in their surrounding environment. Through these experiences, children demonstrated an improved ability to independently assess risk (for example, judging a safe height for climbing or a safe speed for running), initiative in protecting themselves and alerting peers during risky situations, and the ability to transfer this safety knowledge to everyday contexts beyond play. Social interaction among children and the presence of positive role models both adults and peers further supported the internalization of this safety knowledge, indicating that risky play contributes not only to cognitive development but also to the formation of more autonomous safety behavior in early childhood.